Pengaruh Terapi Relaksasi Musik Klasik Terhadap Tekanan Darah Pasien Hipertensi di Ruang Perawatan Interna BLUD Rumah Sakit Konawe - Aidil Shafwan; Mustafa; La Ode Liaumin Azim; Rendi, Rendi (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Hypertension is an increase in systolic blood pressure of at least 140 mmHg or diastolic pressure of at least 90 mmHg. The number of hypertension patients at the Konawe Hospital BLUD from July to December 2021 was 120 cases. Therapy with singing or music is believed to be able to relieve hypertension because it can affect tension so that a person becomes more relaxed. Objective: This study aims to study the effect of classical music therapy on blood pressure in hypertensive patients. Methods: This study was a pre-experimental study with the One Group Pre Test - Post Test Design design on 18 out of 120 populations of hypertension patients in the Konawe Hospital BLUD Internal Care Room from 22 July to 4 August 2022 which were obtained by purposive sampling. The research instrument used a stethoscope to listen to the pulse, a sphygmomanometer to check blood pressure, and a researcher's observation sheet form to record the results of the patient's blood pressure measurements. Data analysis using the Wilcoxon Signed Ranks Test. Results: The average value of post-test blood pressure is lower than the pre-test, namely from stage 1 to the prehypertension category. The results of the analysis showed that there was an effect of giving classical music relaxation therapy on the blood pressure of hypertensive patients. Conclusion: There are differences in blood pressure before and after giving classical music relaxation therapy.